Effects of DOM Chemodiversity on Microbial Diversity in Forest Soils on a Continental Scale - Jian Wang; Lingrui Qu; Helena Osterholz; Yulin Qi; Xiangfeng Zeng; Edith Bai; Chao Wang (Global Change Biology, 2025)
Soil dissolved organic matter (DOM) is a critical reservoir of carbon and nutrients in forest ecosystems, playing a central role in carbon cycling and microbial community dynamics. However, the influence of DOM molecular‐level diversity (chemodiversity) on microbial community diversity and spatial distribution remains poorly understood. In this study, we used Fourier transform ion cyclotron resonance mass spectrometry and high‐throughput sequencing to analyze soil DOM and microbial diversity along a ~4,000 km forest transect in China. We found that soil DOM chemodiversity varies significantly across sites, initially increasing and then decreasing with latitude. Additionally, we observed that the biogeographic distribution of DOM components has differential effects on bacterial and fungal diversity: lipid‐like compounds are strongly associated with bacterial diversity, while aromatic‐, carbohydrate‐, and lipid‐like compounds primarily influence fungal diversity. Linear models and structural equation modeling both reveal that DOM acts as a key intermediary, mediating the effects of temperature and soil properties on microbial spatial distribution. Our findings emphasize the importance of DOM molecular characteristics in shaping microbial community structure and functioning, providing new insights into how environmental factors influence microbial ecosystems and soil carbon cycles in forest ecosystems.